Increased expression of ApoE and protection from amyloid-beta toxicity in transmitochondrial cybrids with haplogroup K mtDNA - Kunal Thaker (Neurobiology of Disease, 2016)
Mitochondrial (mt) DNA haplogroups, defined by specific single nucleotide polymorphism (SNP) patterns, represent populations of diverse geographic origins and have been associated with increased risk or protection of many diseases. The H haplogroup is the most common European haplogroup while the K haplogroup is highly associated with the Ashkenazi Jewish population. Transmitochondrial cybrids (cell lines with identical nuclei, but mtDNA from either H (n = 8) or K (n = 8) subjects) were analyzed by the Seahorse flux analyzer, quantitative polymerase chain reaction (Q-PCR) and immunohistochemistry (IHC). Cybrids were treated with amyloid-β peptides and cell viabilities were measured. Other cybrids were demethylated with 5-aza-2′-deoxycytidine (5-aza-dC) and expression levels for APOE and NFkB2 were measured. Results show K cybrids have (a) significantly lower mtDNA copy numbers, (b) higher expression levels for MT-DNA encoded genes critical for oxidative phosphorylation, (c) lower Spare Respiratory Capacity, (d) increased expression of inhibitors of the complement pathway and important inflammasome-related genes; and (e) significantly higher levels of APOE transcription that were independent of methylation status. After exposure to amyloid-β1–42 peptides (active form), H haplogroup cybrids demonstrated decreased cell viability compared to those treated with amyloid-β42–1 (inactive form) (p < 0.0001), while this was not observed in the K cybrids (p = 0.2). K cybrids had significantly higher total global methylation levels and differences in expression levels for two acetylation genes and four methylation genes. Demethylation with 5-aza-dC altered expression levels for NFkB2, while APOE transcription patterns were unchanged. Our findings support the hypothesis that mtDNA-nuclear retrograde signaling may mediate expression levels of APOE, a key factor in many age-related diseases. Future studies will focus on identification of the mitochondrial-nuclear retrograde signaling mechanism(s) contributing to these mtDNA-mediated differences.